Housing Policy, Wealth Formation and the Singapore Economy - PHANG, Sock-Yong (Institutional Knowledge at Singapore Management University, 2001)
This paper evaluates the contribution of housing policy in Singapore to financial sector development, housing wealth formation and macro-economic performance, both retrospectively and prospectively. It provides an overview of past housing policies and traces the linkages to the financial sector. Housing policy as effected through the Housing and Development Board and the Central Provident Fund (CPF) hampered the development of the commercial housing loans sector and domestic financial markets, but contributed to the overall growth and stability of the housing loans market and associated financial institutions. Housing policy and the trend of housing asset inflation contributed significantly to the formation of both gross and net housing wealth. Economic growth has not suffered from the heavy emphasis on housing investment although various policies that resulted in exogenous shifts in housing demand contributed to increased housing price volatility in the short term. The structure of the housing loans market has also allowed the CPF contribution rate to be more effectively used as an instrument for macro-economic stabilisation.